(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
As competition in higher education becomes more intense, universities in developing countries are forced to take a more strategic approach to marketing. This research explores the impact of marketing approaches on institutional competitiveness, enrolment and sustainability in the face of resource limitations and market competition. Adopting a multi-method approach, the study integrates quantitative measures of enrolment trends with qualitative insights into institutional strategies and policies. Results suggest that institutions adopting data-driven, student-centred, digitally enabled marketing practices demonstrate greater visibility and resilient enrolment strategies than those following traditional administrative practices. Critical success factors are branding, digital marketing, internationalization and market relevance. Yet institutional constraints, such as non-flexible regulatory frameworks and financial constraints continue to hamper marketing strategies in many developing economies. This research builds on existing literature by introducing an integrated model of marketing management in developing countries, and provides insights for improving institutional competitiveness in a highly competitive market.